Alternative discourses in Southeast Asia - Syed Farid Alatas, (Universiti Kebangsaan Malaysia, 2001)
This article brings into focus the question of alternative discourses in the social sciences. Alternative discourses are works that attempt to debunk ideas that have become entrenched in the social sciences, partly as a result of colonialism and the continuing Eurocentrism in the social sciences. In the context of Southeast Asia as well as much of the non-Western world, alternative discourses in the social sciences could also be referred to collectively as counter- Eurocentric social science. This paper discusses the emergence of alternative discourses in Southeast Asia, the defintion of alternative discourse, and the future of these discourses in our region